beta-Glucosidase activity from the thermophilic fungus Scytalidium thermophilum is stimulated by glucose and xylose - Zanoelo, F.F; Polizeli, M. de L.T. de M; Terenzi, H.F; Jorge, J.A (FEMS microbiology letters, 2004)
An inducible mycelial beta-glucosidase from Scytalidum thermophilum was characterized. The enzyme exhibited a pI of 6.5, a carbohydrate content of 15%, and an apparent molecular mass of about 40 kDa. Optima of temperature and pH were 60 degrees C and 6.5, respectively. The enzyme was stable up to 1 h at 50 degrees C and exhibited a half-life of 20 min at 55 degrees C. The enzyme hydrolyzed p-nitrophenyl-beta-D-glucopyranoside, p-nitrophenyl-beta-D-xylopyranoside, o-nitrophenyl-beta-D-galactopyranoside, p-nitrophenyl-alpha-arabinopyranoside, cellobiose, laminaribiose and lactose. Kinetic studies indicated that the same enzyme hydrolyzed these substrates. beta-Glucosidase was activated by glucose or xylose at concentration varying from 50 to 200 mM. The apparent affinity constants (K(0.5)) for glucose and xylose were 36.69 and 43.24 mM, respectively. The stimulatory effect of glucose and xylose on the S. thermophilum beta-glucosidase is a novel characteristic which distinguish this enzyme from all other beta-glucosidases so far described.